Transcriptomic Analysis Provides New Insights into the Tolerance Mechanisms of Green Macroalgae Ulva prolifera to High Temperature and Light Stress - Kifat Jahan; Mst Shamim Ara Supty; Jun-Seok Lee; Keun-Hyung Choi (Biology)
Our research focused on understanding the genetic mechanisms that contribute to the tolerance of Ulva prolifera (Chlorophyta), a marine macroalgae, to the combined stress of high temperature and high light intensity. At the mRNA level, the up-regulated DEGs showed enrichment in pathways related to ribosomes, proteasomes, and peroxisomes. The spliceosome pathway genes were found to be vital for U. prolifera’s ability to adapt to various challenging situations in all the comparison groups. In response to elevated temperature and light intensity stress, there was a significant increase in genes and pathways related to ribosomes, proteasomes, and peroxisomes, whereas autophagy showed an increase in response to stress after 24 h, but not after 48 h. These findings provide novel insights into how U. prolifera adapts to elevated temperature and light stress.